Interleukin-18 and cytotoxic impairment are independent and synergistic causes of murine virus-induced hyperinflammation - Tsoukas, Paul (Blood, 2020)
Hemophagocytic lymphohistiocytosis (HLH) and macrophage activation syndrome (MAS) are life-threatening hyperinflammatory syndromes typically associated with underlying hematologic and rheumatic diseases, respectively. Familial HLH is associated with genetic cytotoxic impairment and thereby to excessive antigen presentation. Extreme elevation of serum interleukin-18 (IL-18) has been observed specifically in patients with MAS, making it a promising therapeutic target, but how IL-18 promotes hyperinflammation remains unknown. In an adjuvant-induced MAS model, excess IL-18 promoted immunopathology, whereas perforin deficiency had no effect. To determine the effects of excess IL-18 on virus-induced immunopathology, we infected Il18-transgenic (Il18tg) mice with lymphocytic choriomeningitis virus (LCMV; strain Armstrong). LCMV infection is self-limited in wild-type mice, but Prf1(−/−) mice develop prolonged viremia and fatal HLH. LCMV-infected Il18-transgenic (Il18tg) mice developed cachexia and hyperinflammation comparable to Prf1(−/−) mice, albeit with minimal mortality. Like Prf1(−/−) mice, immunopathology was largely rescued by CD8 depletion or interferon-γ (IFNg) blockade. Unlike Prf1(−/−) mice, they showed normal target cell killing and normal clearance of viral RNA and antigens. Rather than impairing cytotoxicity, excess IL-18 acted on T lymphocytes to amplify their inflammatory responses. Surprisingly, combined perforin deficiency and transgenic IL-18 production caused spontaneous hyperinflammation specifically characterized by CD8 T-cell expansion and improved by IFNg blockade. Even Il18tg;Prf1-haplosufficient mice demonstrated hyperinflammatory features. Thus, excess IL-18 promotes hyperinflammation via an autoinflammatory mechanism distinct from, and synergistic with, cytotoxic impairment. These data establish IL-18 as a potent, independent, and modifiable driver of life-threatening innate and adaptive hyperinflammation and support the rationale for an IL-18–driven subclass of hyperinflammation.